Cerebrovascular reserve in moyamoya disease: relation to cerebral blood flow, capillary dysfunction, oxygenation, and energy metabolism - Svedung Wettervik, Teodor; Fahlström, Markus; Wikström, Johan; Lewén, Anders; Enblad, Per (Frontiers in Neurology, 2023)
Background Cerebral hemodynamics in moyamoya disease (MMD) is complex and needs further elucidation. The primary aim of the study was to determine the association of the cerebrovascular reserve (CVR) with cerebral blood flow (CBF) disturbances, oxygen extraction fraction (OEFmax), and energy metabolism (CMRO2max) in MMD, using arterial spin label magnetic resonance imaging (ASL-MRI) before and after acetazolamide administration. Methods Thirty-nine ASL-MRI scans with a concurrent acetazolamide challenge from 16 MMD patients at the Uppsala University Hospital, Sweden, 2016–2021, were retrospectively analyzed. CBF was assessed before and 5, 15, and 25 min after acetazolamide administration, and the maximal response CVRmax was used for further analyses. Dynamic susceptibility contrast (DSC) MRI was performed 30 min after acetazolamide injection, and the data were analyzed using the Cercare Medical Neurosuite to assess capillary transit time heterogeneity (CTTH; indicating microvascular function), OEFmax, and CMRO2max. Results In the ACA territory, a lower CVRmax was associated with lower baseline CBF, higher CTTH, and higher OEFmax but not with CMRO2max in generalized estimating equation models. In the MCA territory, lower CVRmax was associated with lower baseline CBF and higher CMRO2max but not with CTTH and OEFmax.. Conclusion Altogether, a compromised CVR in MMD patients reflected disturbances in macro-/microvascular blood flow, oxygenation, and CMRO2. ASL-MRI with acetazolamide challenge is a feasible and radiation-free alternative to positron emission tomography (PET) imaging in MMD.